Exposure of Keratinocytes to Candida Albicans in the Context of Atopic Milieu Induces Changes in the Surface Glycosylation Pattern of Small Extracellular Vesicles to Enhance Their Propensity to Interact With Inhibitory Siglec Receptors - Kobiela, Adrian; Frackowiak, Joanna E.; Biernacka, Anna; Hovhannisyan, Lilit; Bogucka, Aleksandra E.; Panek, Kinga; Paul, Argho Aninda; Lukomska, Joanna; Wang, Xinwen; Giannoulatou, Eleni; Krolicka, Aleksandra; Zielinski, Jacek; et al. (Frontiers in Immunology, 2022)
Candida albicans (C. albicans) infection is a potential complication in the individuals with atopic dermatitis (AD) and can affect clinical course of the disease. Here, using primary keratinocytes we determined that atopic milieu promotes changes in the interaction of small extracellular vesicles (sEVs) with dendritic cells and that this is further enhanced by the presence of C. albicans. sEV uptake is largely dependent on the expression of glycans on their surface; modelling of the protein interactions indicated that recognition of this pathogen through C. albicans-relevant pattern recognition receptors (PRRs) is linked to several glycosylation enzymes which may in turn affect the expression of sEV glycans. Here, significant changes in the surface glycosylation pattern, as determined by lectin array, could be observed in sEVs upon a combined exposure of keratinocytes to AD cytokines and C. albicans. This included enhanced expression of multiple types of glycans, for which several dendritic cell receptors could be proposed as binding partners. Blocking experiments showed predominant involvement of the inhibitory Siglec-7 and -9 receptors in the sEV-cell interaction and the engagement of sialic acid-containing carbohydrate moieties on the surface of sEVs. This pointed on ST6 β-Galactoside α-2,6-Sialyltransferase 1 (ST6GAL1) and Core 1 β,3-Galactosyltransferase 1 (C1GALT1) as a potential enzymes involved in the process of remodelling of the sEV surface glycans upon C. albicans exposure. Our results suggest that, in combination with atopic dermatitis milieu, C. albicans promotes alterations in the glycosylation pattern of keratinocyte-derived sEVs to interact with inhibitory Siglecs on antigen presenting cells. Hence, a strategy aiming at this pathway to enhance antifungal responses and restrict pathogen spread could offer novel therapeutic options for skin candidiasis in AD.